Gastrointestinal function in chronic radiation enteritis--effects of loperamide-N-oxide. Issue 4 (April 1993) - Yeoh, E K; Horowitz, M; Russo, A; Muecke, T; Robb, T; Chatterton, B E
Abstract : The effects of loperamide-N-oxide, a new peripheral opiate agonist precursor, on gastrointestinal function were evaluated in 18 patients with diarrhoea caused by chronic radiation enteritis. Each patient was given, in double-blind randomised order, loperamide-N-oxide (3 mg orally twice daily) and placebo for 14 days, separated by a washout period of 14 days. Gastrointestinal symptoms; absorption of bile acid, vitamin B12, lactose, and fat; gastric emptying; small intestinal and whole gut transit; and intestinal permeability were measured during placebo and loperamide-N-oxide phases. Data were compared with those obtained in 18 normal subjects. In the patients, in addition to an increased frequency of bowel actions (p < 0.001), there was reduced bile acid absorption, (p < 0.001) a higher prevalence of lactose malabsorption (p < 0.05) associated with a reduced dietary intake of dairy products (p < 0.02), and faster small intestinal (p < 0.001) and whole gut transit (p < 0.05) when compared with the normal subjects. There was no significant difference in gastric emptying between the two groups. Treatment with loperamide-N-oxide was associated with a reduced frequency of bowel actions (p < 0.001), slower small intestinal (p < 0.001), and total gut transit (p < 0.01), more rapid gastric emptying (p < 0.01), improved absorption of bile acid (p < 0.01), and increased permeability to 51Cr EDTA (p < 0.01). These observations indicate that: (1) diarrhoea caused by chronic radiation enteritis is associated with more rapid intestinal transit and a high prevalence of bile acid and lactose malabsorption, and (2) loperamide-N-oxide slows small intestinal transit, increases bile acid absorption, and is effective in the treatment of diarrhoea associated with chronic radiation enteritis.